The role of mechanical ventilation during extracorporeal circulation in children with congenital heart disease - L. Moshkivska; E. Nastenko; S. Khemio Arnes; S. Boyko; V. Lazoryshynetz (Ukrainian Journal of Cardiovascular Surgery, 2017)
The current work is dedicated to the influence of mechanical ventilation on respiratory and mechanical function of lungs during cardiopulmonary bypass in children with congenital heart diseases. The analysis of immunological parameters in the groups during the intraoperative period was carried out and the number of pulmonary complications in the postop-erative period was analyzed.The objective of this work was to study the effect of mechanical ventilation on lungs’ function and postoperative pulmonary complications during cardioplegic cardiac arrest and artificial circulation. 104 patients were included in the research. They were divided into two groups: the study group with 34 (32.7%) patients and the control group with 70 (67.3%). The application of therapeutic and preventive measures allowed us to reduce the severity and the number of pulmonary dysfunctions, to prevent the ventilation volume decreasing, due to a loss in pulmonary capillary permeability and a decrease in lung compliance.